Analisis Hukum Pelaksanaan dan Pelayanan Bagi Pengguna Jaminan Kesehatan Menurut UU No. 24 Tahun 2011 Tentang Badan Penyelenggara Jaminan Sosial - Ervina Sari Sipahutar (Universitas Medan Area, 2020)
BPJS services for public health insurance and BPJS users get their rights in accordance with BPJS procedures and implementation. This paper will discuss the implementation of health services for BPJS users in Medan based on Law No. 24 of 2011 concerning Health Insurance. The research objective is to obtain the Procedure for Registration to Become BPJS Health Participants, the health service system and the Rights of BPJS User Participants. The research method is a type of normative and empirical law research, so that the research and data collected methods used are library methods, a method or a way to collect data using materials, both sourced from primary and secondary data. The results obtained are participants from BPJS itself, not limited to age and certain community groups. All citizens can become BPJS participants even compulsory for those who meet certain conditions. An important part of a health service is available and adhered to standards, because quality health care is if the service is carried out according to existing standards. The role of quality standards in health services is very important to be able to approach the quality assurance in health services for the community. Some BPJS participants responded that there was no distinction between BPJS Health membership patients and general patients. Some participants were quite satisfied with the response of health workers who gave quick and responsive reactions in responding to patient complaints.